Effects of Hydrogels on Soil Moisture, Nutrient Availability and Growth of Sesbania sesban and Cajanus cajan in Semi Arid Zone of Kongelai, West Pokot County - Cheruiyot , Gilbert; Ng’etich , Wilson; Mburu , Francis; Sirmah , Peter; Mengich , Edward; Kimaiyo , Sylvester (African Journal of Education,Science and Technology (AJEST), 2013)
Studies on the effects of hydrogels on soil amendments, moisture conservation, nutrients release and growth of Sesbania sesban and Cajanus cajan in arid and semi-arid lands was carried out. Seedlings of S. sesban and C. cajan were established both in the nursery and in the field with and without hydrogels. Field experiment was carried out under hedgerow intercropping system with three replications and three concentration hydrogels levels (7g, 11g and 15g). In the nursery, root collar diameter (RCD) and heights for each seedling were measured every two weeks up to eight weeks. Seedlings established without hydrogels in the nursery were transplanted into field soils with none, 7g, 11g and 15g of hydrogels. Root collar diameter and height were again measured every month for three months. In addition, soil was collected randomly once every month from the base of each seedling and analyzed for soil moisture and nutrient content. All data were subjected to analysis of variance. Results showed that there was a significant difference in the height and RCD among the three species and at different level of hydrogels. This suggests that use of hydrogels in the nursery soils retards plant growth but improves growth in the field. Hydrogels increased soil moisture content transplanting. Analysis of variance of nutrients release into the soil shows that hydrogels has an effect on the nutrients. Nutrient increased from 0.95, 0.07 and 0.12% in the pre-test analysis to 4.48, 3.81 and 0.42% after analysis in potassium, nitrogen and phosphorus respectively in the soil after transplanting. It was concluded that hydrogels do not contribute to growth of seedlings in the nursery but it does so after transplanting. Hydrogels increase soil moisture and nutrients in the soil therefore recommended for use in semi arid lands to boost the survival and growth of seedlings.